2008
DOI: 10.1111/j.1365-2982.2008.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study of irritable bowel syndrome in a non‐Western population

Abstract: Previous studies have found no female predominance in irritable bowel syndrome (IBS) in non-Western countries. The aim of the study was to assess the prevalence and correlates of Rome II (IBS) in both sexes in Pakistan. A Population-based survey in a low-income inner city area using questionnaires to diagnose Rome II IBS and assess distress, disability and stressful life events. Data were collected from 880/938 (93%) randomly selected residents. 13.4% of women and 13.1% men met criteria for Rome II IBS; 34 (3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 39 publications
(72 reference statements)
7
55
2
Order By: Relevance
“…The marital status was not significant in the current study in accordance with previous research [17] The rate of an organic lesion on colonoscopy among patients with irritable bowel syndrome and no red flag signs was not higher as compared to healthy controls ranging from 10-40% [19,20]. By contrast: during the year following the diagnosis of irritable bowel syndrome the diagnosis of inflammatory bowel diseases was 9-16 times higher [21][22][23][24].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The marital status was not significant in the current study in accordance with previous research [17] The rate of an organic lesion on colonoscopy among patients with irritable bowel syndrome and no red flag signs was not higher as compared to healthy controls ranging from 10-40% [19,20]. By contrast: during the year following the diagnosis of irritable bowel syndrome the diagnosis of inflammatory bowel diseases was 9-16 times higher [21][22][23][24].…”
Section: Discussionsupporting
confidence: 76%
“…The current study documented a prevalence of irritable bowel syndrome [IBS] in 14.1%, similar to studies in Riyadh Saudi Arabia [17] that reported a prevalence of 11.4% among adults. In the present study, the comment age group of IBS patients was 30-50 years old similar to the above study.…”
Section: Discussionsupporting
confidence: 70%
“…A survey carried out in Pakistan [7] concluded the association of irritable bowel syndrome with high income and few years of education in contradiction to the present data.…”
Section: Discussioncontrasting
confidence: 54%
“…The prevalence of IBS in Asia is reportedly 5-9% [2][3][4][5][6][7][8][9][10][11][12][13], while in Western countries it is 10-20% [14][15][16][17][18][19][20][21][22][23][24][25]. Furthermore, no female predominance was found in Asian IBS patients [2], in contrast to in Western IBS patients [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal bloating is a more common complaint than pain in Asians, and this abdominal pain is localized to the upper abdomen rather than in the lower abdomen like it is in Western patients. Moreover, alteration in bowel habits is much less prominent in Asian IBS patients than in Western patients [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%